Perceived stress and coping strategies in clinical practice among B. Sc. Nursing students at college of nursing, PIMS (DU), Loni - Vinayak Dighe, Sharadchandra (International Journal of Nursing Research, 2023)
Introduction: Evidence reports that undergraduate nursing students’ experiences moderate to high stress. Clinical posting is a major stressor for them because they are supposed to carry out a variety of tasks such as taking care of patients, completing assignments, responding to teachers and staff nurses etc. Stress may affect their health, academic and clinical performance. Methodology: the Descriptive cross-sectional study was undertaken to assess the stress and coping strategies among B. Sc. Nursing students in clinical practice. 55 participants were selected by adapting random sampling (lottery) method. Data were collected by using self-administered Perceived stress scale and Coping strategy inventory developed by Sheu et al. (1997). Results: Findings of the study revealed that male and female participants were 50.9% and 49.09% respectively. 32.72% of the participants were aged 20 years, 36.36% of the participants were studying in second year B. Sc. Nursing, and most of them i.e. 96.36% participants have interest in nursing. The majority (78.18%) of the participants’ experiences moderate level of stress. Taking care of patients (mean 11.12 ±5.78) and stress from teachers and nursing staff (mean 11.12 ± 4.11) are the major stressors for them. Participants mostly used problem-solving (mean 16.01 ± 4.73) and staying optimistic (mean 10.38 ± 3.00) coping strategies to overcome their stress. Conclusion: It is concluded that nursing students experience moderate level of stress. Equipping students with clinical knowledge and skills, appropriate communication and interpersonal relation skills can be instrumental in relieving stress and effective coping.